Learning Styles In Differentiated Instructions Are Mistakes: A Literature Study - Muhammad Sobirin (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Differentiated learning aims to accommodate students' diverse needs, abilities, and preferences in the educational process. However, the concept of "learning styles" has been a persistent yet controversial approach within this framework. This literature study critically examines the validity of learning styles as a foundation for differentiated instruction. Drawing on a wide range of research, it explores the scientific evidence (or lack thereof) supporting learning styles and highlights the potential pitfalls of relying on this concept in teaching practices. The findings reveal that while differentiated learning remains a crucial strategy, basing it on learning styles can lead to misconceptions and ineffective methods. The study concludes by offering evidence-based recommendations for educators to implement differentiated learning without the misconceptions associated with learning styles, focusing on strategies that enhance student engagement and learning outcomes.